Numerical Modeling of Complex Targets for High-Energy- Density Experiments with Ion Beams and other Drivers. (March 2016) - Koniges, Alice; Liu, Wangyi; Lidia, Steven; Schenkel, Thomas; Barnard, John; Friedman, Alex; Eder, David; Fisher, Aaron; Masters, Nathan
Abstract: We explore the simulation challenges and requirements for experiments planned on facilities such as the NDCX-II ion accelerator at LBNL, currently undergoing commissioning. Hydrodynamic modeling of NDCX-II experiments include certain lower temperature effects, e.g., surface tension and target fragmentation, that are not generally present in extreme high-energy laser facility experiments, where targets are completely vaporized in an extremely short period of time. Target designs proposed for NDCX-II range from metal foils of order one micron thick (thin targets) to metallic foam targets several tens of microns thick (thick targets). These high-energy-density experiments allow for the study of fracture as well as the process of bubble and droplet formation. We incorporate these physics effects into a code called ALE-AMR that uses a combination of Arbitrary Lagrangian Eulerian hydrodynamics and Adaptive Mesh Refinement. Inclusion of certain effects becomes tricky as we must deal with non-orthogonal meshes of various levels of refinement in three dimensions. A surface tension model used for droplet dynamics is implemented in ALE-AMR using curvature calculated from volume fractions. Thick foam target experiments provide information on how ion beam induced shock waves couple into kinetic energy of fluid flow. Although NDCX-II is not fully commissioned, experiments are being conducted that explore material defect production and dynamics.